Sustainability assessment : criteria and processes - Gibson, Robert B., 1950- (Earthscan, 2005)
This work tackles the complexities of sustainability assessment and provides practical solutions and comprehensive analysis, guidance and criteria for impact assessment professionals and policy makers at all levels and in all circumstances.